2021
DOI: 10.3389/fonc.2021.653246
|View full text |Cite
|
Sign up to set email alerts
|

An Essential NRP1-Mediated Role for Tagln2 in Gastric Cancer Angiogenesis

Abstract: Knowledge about the precise biological role and underlying mechanism of Tagln2 in tumor progression is relatively limited, especially in angiogenesis focused on tumor derived endothelial cells (ECs) has rarely been reported. Here, the function, molecular mechanism and potential clinical value of Tagln2 in gastric cancer (GC) angiogenesis were investigated. GC tissue microarrays were used to assess the expression of Tagln2 in ECs. The relationships between expression and clinicopathological features were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Our results were further reinforced by the IHC analysis from HPA. These results were in accordance with previous reports regarding colorectal cancer 8 , gastric cancer 30 , bladder cancer 34 , clear cell renal cell carcinoma 35 , glioma 36 , and breast cancer 37 . Meanwhile, in patients having BLCA, KICH, KIRC, LIHC, LUSC, PAAD, TGCT, and THCA, TAGLN2 expression was analyzed to be correlated with the advanced cancer stage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were further reinforced by the IHC analysis from HPA. These results were in accordance with previous reports regarding colorectal cancer 8 , gastric cancer 30 , bladder cancer 34 , clear cell renal cell carcinoma 35 , glioma 36 , and breast cancer 37 . Meanwhile, in patients having BLCA, KICH, KIRC, LIHC, LUSC, PAAD, TGCT, and THCA, TAGLN2 expression was analyzed to be correlated with the advanced cancer stage.…”
Section: Discussionsupporting
confidence: 93%
“…TAGLN2, located on the human chromosome 1q23.2 region, is a member of the transgelins family and encodes a 199 amino acid protein. Studies on TAGLN2 in the context of tumor progression have garnered considerable interest due to its ability to modulate the tumor microenvironment and promote tumor angiogenesis 30 , 31 , invasion, and metastasis 32 , 33 . Nevertheless, the exact mechanism of TAGLN2 in cancers remains largely unknown and research into it is still in its early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Among the tumors from 33 different types of cancer investigated present in TCGA and the GTEX databases, NRP1 was highly expressed in 19 tumors and lowly expressed in 14 tumors. Some previous studies on NRP1 have shown that upregulation of TAGLN2 leads to a significant increase in the messenger RNA and protein levels of NRP1 in gastric cancer, 14 and activation of NRP1/ VEGFR2 and downstream MAPK signaling pathways promotes gastric cancer cell proliferation and motility. Meanwhile, in esophageal cancer studies, microRNA-124 inhibited cancer cell proliferation by negatively regulating NRP1.…”
Section: Discussionmentioning
confidence: 92%
“…Each of the markers we identified have previously been linked to human cancer, and thus are not limited in relevance to the murine model employed. Of these, Tagln2 has previously been linked to angiogenesis, proliferation, migration, and epithelial–mesenchymal transition in GC [ 25 , 26 ], while Mbl2 gene variants have been linked to risk of stomach cancer [ 27 ] and increased serum levels linked to pancreatic cancer [ 28 ]. In addition, Itih3 has previously been identified as a predictor of GC in mice and patients [ 29 ], while F12 is a prognostic marker for thyroid cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%